Analisis Pengaruh Ukuran Perusahaan, Ukuran Dewan Komisaris, Profitabilitas, Dan Leverage Terhadap Pengungkapan Tanggung Jawab Sosial Pada Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2016 - Indrayenti Indrayenti; Jenny Jenny (Jurnal Akuntansi dan Keuangan, 2018)
This study aims to analyze the influence of the size of the company, the board of commissioners, profitability and leverage. On the disclosure of corporate social responsibility in the mining industry sector. The independent variable in this study is the size of the company, the board of commissioners, profitability and leverage. And the dependent variable is the Disclosure of Social Responsibility / CSRD.The sample of this study is mining companies and industry sectors listed in Indonesia stock Exchange in the period 2014-2016. The Total of the corporation in this study a total of 13 companies. Test hypothesis with multiple regression analysis. The results of the multiple regression analysis showed that the size of the company, the board of commissioners, profitability and leverage affect positively on the Disclosure of Social Responsibility. The value of the Adjusted R2 of the regression model is 0,518 It means that 51.8% of corporate social responsibility disclosure can be explained by the size of the company, the board of commissioners, profitability, and leverage.